Evaluating Measures of Hospital Quality: Evidence from Ambulance Referral Patterns - Doyle, Joseph; Graves, John; Gruber, Jonathan (The Review of Economics and Statistics, 2019)
Hospital quality measures are crucial to a key idea behind health care payment reforms: "paying for quality" instead of quantity. Nevertheless, such measures face major criticisms largely over the potential failure of risk adjustment to overcome endogeneity concerns when ranking hospitals. In this paper we test whether patients treated at hospitals that score higher on commonly-used quality measures have better health outcomes in terms of rehospitalization and mortality. To compare similar patients across hospitals in the same market, we exploit ambulance company preferences as an instrument for hospital choice. We find that a variety of measures used by insurers to measure provider quality are successful: choosing a high-quality hospital compared to a low-quality hospital results in 10-15% better outcomes.